2017
DOI: 10.1128/aac.01605-16
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Replication Rate Modulation in Combination with Antimicrobial Therapy: Turning the Microbe against Itself

Abstract: A major clinical challenge for treating infectious diseases is the duration of antimicrobial therapy required to eradicate the pathogen. We hypothesized that modulation of the bacterial replication rate in the context of an antimicrobial exposure is coupled with the rate and extent of bactericidal effects. Herein we describe results from in vitro infection model (one compartment, 24-h model; hollow fiber, 10-day model) studies designed to probe the relationship between the bacterial replication rate and the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…With regard to bacterial-growth-rate modulation, recent studies have suggested that speeding up bacterial replication in the context of effective antimicrobial exposure increases the rate and extent of bactericidal activity and shortens therapy duration (5,6). In the context of ineffective antimicrobial exposure, such regimens increased bactericidal activity early in the course of therapy but ultimately failed due to antibioticresistant bacterial subpopulations (6).…”
mentioning
confidence: 99%
“…With regard to bacterial-growth-rate modulation, recent studies have suggested that speeding up bacterial replication in the context of effective antimicrobial exposure increases the rate and extent of bactericidal activity and shortens therapy duration (5,6). In the context of ineffective antimicrobial exposure, such regimens increased bactericidal activity early in the course of therapy but ultimately failed due to antibioticresistant bacterial subpopulations (6).…”
mentioning
confidence: 99%
“…There has been renewed interest in therapeutic and adjuvant alternatives to small molecule antibacterial agents. Among these are phage therapies [19,20], virulence inhibitors [19,21], bacterial growth rate modulators [22][23][24], monoclonal antibodies [25][26][27], and other approaches for meeting the challenge of antibiotic resistance. Of the 37 programs in the CARB-X portfolio for antibacterial treatment, over 48% are alternatives to traditional small molecule antibacterial agents [28].…”
Section: Phage Therapies Virulence Inhibitors Bacterial Growth Ratementioning
confidence: 99%
“…W e previously evaluated the relationship between the bacterial replication rate and the rate and extent of bactericidal effects in the context of an effective antibiotic exposure (1). In brief, the studies utilized in vitro infection models (a one-compartment, 24-h model; a hollow-fiber, 10-day model) where the bacterial replication rate was modulated using sodium chloride.…”
mentioning
confidence: 99%